2008
DOI: 10.1016/j.ijpara.2007.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the muscarinic agonist, 5-methylfurmethiodide, on contraction and electrophysiology of Ascaris suum muscle

Abstract: Contraction and electrophysiological effects of 5-methylfurmethiodide (MFI), a selective muscarinic agonist in mammals, were tested on Ascaris suum muscle strips. In a contraction assay, MFI produced weak contraction and was less potent than levamisole and acetylcholine. Atropine (3 µM) a nonselective muscarinic antagonist in mammalian preparations, did not affect contractions produced by MFI. Mecamylamine (3 µM) a nicotinic antagonist in A. suum preparations, blocked the MFI contractions indicating that MFI h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The rise in cytosolic calcium following opening of AChRs by levamisole then produces muscle contraction mediated by the calcium contraction coupling pathway 46 , 49 , 50 . TRP channels (TRP-2, GON-2 and CED-11) channels present in Brugia muscle also contribute to the muscle contraction 16 , 51 , 52 . TRP channels are subject to regulation by intracellular messengers including direct or indirect activation and inhibition by calcium and PKC 51 , 53 , 54 , Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The rise in cytosolic calcium following opening of AChRs by levamisole then produces muscle contraction mediated by the calcium contraction coupling pathway 46 , 49 , 50 . TRP channels (TRP-2, GON-2 and CED-11) channels present in Brugia muscle also contribute to the muscle contraction 16 , 51 , 52 . TRP channels are subject to regulation by intracellular messengers including direct or indirect activation and inhibition by calcium and PKC 51 , 53 , 54 , Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In contraction assay and electrophysiological recordings from A. suum muscle, pyrantel > bephenium > levamisole > acetylcholine (Harrow and Gration, 1985; Martin et al ., 2004; Trailovic et al ., 2008). In reconstituted Haemonchus contortus L-AChRs, levamisole > acetelcholine > pyrantel in Hco-L-AChR1 subtype and in the Hco-L-AChR2 subtype, pyrantel > acetylcholine > levamisole (Boulin et al ., 2011).…”
mentioning
confidence: 99%
“…Our expression data are consistent with results from whole-cell patch-clamp studies in B. malayi that found that AChRs are activated by cholinergic anthelmintics (levamisole, pyrantel, bephenium and tribendimidine) and that levamisole reversibly paralyzed adult worms ( Robertson et al., 2011 ). Biophysical and pharmacological features of body muscle ACh receptors in B. malayi ( Robertson et al., 2011 , 2013 ) suggest that the B. malayi AChRs are different from those in A. suum [( Martin et al., 2004; Trailovic et al., 2008 ) and H. contortus ( Boulin et al., 2011 ) and possibly more similar to those in C. elegans ( Boulin et al., 2008 ). The B. malayi AChRs in body muscle are less sensitive to both acetylcholine and levamisole than that in C. elegans , A. suum or O. dentatum ( Robertson et al., 2011 ).…”
Section: Resultsmentioning
confidence: 98%